Digital Transformation in Arabic Language Learning: Enhancing Vocabulary Acquisition through H5P Interactive Video - Baiq Raudatussolihah; Ali Fathurrahman (Journal of Digital Arabic Language Education, 2026)
The rapid growth of digital technology has significantly transformed language education, including Arabic language learning in both formal and non-formal educational institutions. One of the most challenging aspects in Arabic learning is vocabulary acquisition because students often experience difficulties in memorizing, understanding, and applying vocabulary in authentic communication contexts. This study explores the role of H5P Interactive Video as an innovative digital learning medium in enhancing Arabic vocabulary acquisition among students. The research employs a qualitative library research design supported by recent empirical studies related to educational technology, interactive multimedia, and Arabic language pedagogy. Data were collected from scholarly journals, books, and recent studies published between 2020 and 2025. The findings reveal that H5P Interactive Video contributes positively to vocabulary mastery through interactive quizzes, immediate feedback, audiovisual stimulation, contextual learning experiences, and learner-centered activities. Furthermore, the integration of H5P promotes students’ motivation, engagement, autonomy, and retention of Arabic vocabulary. Interactive digital learning environments also support constructivist and multimedia learning theories by combining visual, auditory, and kinesthetic elements in one platform. Despite several challenges such as technological readiness, internet accessibility, and teacher digital literacy, H5P Interactive Video remains a promising innovation in Arabic language education. This study concludes that digital transformation through H5P Interactive Video can significantly enhance vocabulary acquisition and create more meaningful Arabic learning experiences in the twenty-first century educational environment.